Evolutionary transformation of the journal. Part 4 - Michał Kokowski (Studia Historiae Scientiarum)
The article presents the fourth phase of the development of the journal Studia Historiae Scientiarum (previous name Prace Komisji Historii Nauki PAU / Proceedings of the PAU Commission on the History of Science). The sections of the journal were modified, as well as the peer review procedure and the bibliographic style. There has also been an increase in the number of foreign authors and reviewers of the journal.